Shared genetic risk and causal associations between Post-traumatic stress disorder and migraine with antithrombotic agents and other medications - Charlotte K. Bainomugisa; Dagmar Bruenig; Heidi G. Sutherland; Lyn R. Griffiths; Dale R. Nyholt; Divya Mehta (Neurobiology of Stress)
Post-traumatic stress disorder (PTSD) is a psychiatric disorder that frequently co-occurs with pain disorders including migraine. There are proposed biological, genetic and environmental factors associated with both PTSD and migraine suggesting shared etiology. Genome-Wide Association Studies (GWAS) have been used to identify genomic risk loci associated with various disorders and to investigate genetic overlap between traits. There is a significant genetic correlation between PTSD and migraine with no evidence of a causal relationship that could be attributed to pleiotropy. Cross-disorder genetic analyses were applied to investigate the genetic overlap and causal associations using GWAS summary statistics of PTSD (n = 214408), migraine (n = 873341) and 23 medication use traits (n = 78808–305913) including anti-depressants, anti-migraine preparations and beta-blocking agents.Across the entire genome, anti-thrombotic agents had a significant and negative genetic correlation with PTSD (rG = −0.2, PFDR = 0.032) and a positive genetic correlation with migraine (rG = 0.26, PFDR = 2.23 x 10−8). PTSD showed significant genetic correlation with 11 other medication use traits including beta blocking agents (rG = −0.11, PFDR = 0.034). Of the 2495 genomic regions tested, PTSD showed significant local genetic correlation with 12 medication use traits at 43 loci; while migraine showed significant genetic correlation with only anti-inflammatory agents and anti-rheumatic products at locus 12:57522282–57607142 (DAB1) (P < 2 x 10−5). The genetic liability to PTSD had a causal effect on increased risk of using pain medication such as opioids (βivw = 0.59, P = 5.21 x 10−5) while the genetic liability to migraine had a causal effect on the increased risk of using anti-thrombotic agents (βivw = 0.59, P = 1.69 x 10−7). The genes in the genomic regions shared between PTSD and medication use traits were enriched in neural-related pathways such as neuron development, neurogenesis and protein kinase activity. These results provide further insight into the genetically controlled biological and environmental factors underlying the shared etiology between PTSD and migraine. The identified biomarkers can be used as a basis for investigation as potential drug targets for both disorders. These findings are significant for drug re-purposing and treatment of PTSD and migraine using monotherapy.